2008
DOI: 10.1080/13825580701336874
|View full text |Cite
|
Sign up to set email alerts
|

Identity and Location Priming Effects and their Temporal Stability in Young and Older Adults

Abstract: Unlike previous studies, the present experiment was designed to directly compare negative (NP) and positive priming (PP) in 37 young (mean age: 21.5 years) and 37 older adults (mean age: 69.4 years) by means of two independent identity- and location-based priming tasks. While identity PP was shown to be reduced in older adults, no age-related differences were found for location PP. This pattern of results supports the notion that mechanisms involved in identity- and location-based PP are largely independent of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
(110 reference statements)
1
1
0
Order By: Relevance
“…An early review by Verhaeghen and De Meersman (1998) reported no effect of age for location-based NP, this means comparable NP effects for young and OA. Some recent studies support the findings of Verhaeghen and De Meersman (1998) and find a reliable location-based NP effect in OA (McAuliffe et al, 2006; Troche et al, 2008). However, decreased response times for location-based NP in older subjects have also been reported (Witthöft et al, 2009).…”
Section: Introductionsupporting
confidence: 58%
“…An early review by Verhaeghen and De Meersman (1998) reported no effect of age for location-based NP, this means comparable NP effects for young and OA. Some recent studies support the findings of Verhaeghen and De Meersman (1998) and find a reliable location-based NP effect in OA (McAuliffe et al, 2006; Troche et al, 2008). However, decreased response times for location-based NP in older subjects have also been reported (Witthöft et al, 2009).…”
Section: Introductionsupporting
confidence: 58%
“…Consistent with the claim that aging is accompanied by reduced inhibitory control, several studies using negative priming paradigms have revealed that older adults do not show negative priming (Connelly & Hasher, 1993, Experiment 3; Hasher et al, 1991; Kane, Hasher, Stoltzfus, Zacks, & Connelly, 1994; Kane, May, Hasher, Rahhal, & Stoltzfus, 1997; McDowd & Oseas-Kreger, 1991; Stoltzfus, Hasher, Zacks, Ulivi, & Goldstein, 1993; Tipper, 1991; Witthöft, Sander, Süβ, & Wittmann, 2009) or that they show reduced negative priming relative to young adults (Earles et al, 1997) when identity is the relevant target dimension. An equally telling number of studies have shown otherwise (Andrés et al, 2008; Borella, Delaloye, Lecerf, Renaud, & De Ribaupierre, 2009; Gamboz, Russo, & Fox, 2000; Grant & Dagenbach, 2000; Hogge, Salmon, & Collette, 2008; Intons-Peterson, Rocchi, West, McLellan, & Hackney, 1998; Kieley & Hartley, 1997; Kramer et al, 1994; Kramer & Strayer, 2001; Langley, Overmier, Knopman, & Prod'Homme, 1998; Little & Hartley, 2000; Pesta & Sanders, 2000; Schelstraete & Hupet, 2002; Schooler, Neumann, Caplan, & Roberts, 1997; Simone & McCormick, 1999; Sullivan & Faust, 1993; Sullivan, Faust, & Balota, 1995; Titz, Behrendt, Menge, & Hasselhorn, 2008; Troche, Gibbons, & Rammsayer, 2008; Vakil, Manovich, Ramati, & Blachstein, 1996; Van der Linden et al, 1999).…”
Section: Unimodal Paradigmsmentioning
confidence: 99%